Implementation of the Lesson Study for Learning Community-Based GDL Model on Student Learning Outcomes - Andromeda Andromeda; Leli Astuti; Yerimadesi Yerimadesi; Yulia Asri Warlinda (Jurnal Penelitian Pendidikan IPA, 2023)
The purpose of the study was to analyze the effect of the LSLC-based GDL learning model on the reaction rate material on student learning outcomes at SMAN 1 Linggabayu. This type of research used quasi-experimental research design, namely pretest-posttest control group design. The population consists of students of class XI MIPA at SMAN 1 Linggabayu in the academic year 2021/2022. The sample was selected using random sampling technique, and the sample classes were XI MIPA 1 and XI MIPA 4. The instrument used in this study was a test instrument in the form of multiple-choice questions consisting of 20 questions with 5 answer choices. The data analysis technique used the n-gain test, normality test, F test and hypothesis testing (t test). The average learning outcomes of experimental and control class students were 81 and 72, respectively. From the results of the study, the n-gain value in the experimental class was 0.74 in the high category while the control class was 0.61 in the medium category. At a significance level of 0.05, the value of tcount > ttable. So, the application of the guided discovery learning model based on lesson study for the learning community has an influence on improving student learning outcomes.